Retreatment of oval-shaped root canals filled with TotalFill bioceramic or AH plus sealer - Ahmed Jamleh; Mohannad Nassar; Abdulmohsen Alfadley; Azhar Alanazi; Hadeel Alotiabi; Maryam Alghilan; Khalid Alfouzan (Scientific Reports, 2023)
Abstract This study investigated retreatment of oval canals filled with gutta-percha and different sealers using WaveOne Gold (WOG). Single oval canals were prepared to size 30, 0.04 and obturated with gutta percha and AH Plus (AHP) or TotalFill bioceramic (TFBC) sealer. After 6-month incubation, the canals were retreated with WOG Primary (25, 0.07) under simulated body temperature, and the developed load and torque were simultaneously measured. The time and regaining the apical patency were checked. Micro-computed tomography scanning was performed to calculate the remaining obturating materials. An independent t-test and chi-square test were performed at a 95% confidence level. A shorter retreatment time was needed in TFBC than in AHP (P = 0.003). However, a higher maximum apical load was reported with AHP (P = 0.000). Meanwhile, comparable maximum coronal load and maximum torque values were observed. Apical patency was regained in all TFBC roots and only 75% of the AHP samples (P = 0.217). The remaining obturating materials were comparable in TFBC (13.02 ± 8.12%) and AHP (10.11 ± 8.46%) (P = 0.398). WOG was able to remove 89.89% and 86.98% of obturating materials in TFBC and AHP, respectively. The TFBC presented lower apical loads and faster retreatment compared to AHP.